The Needs Analysis of The Develop of Biology Module Based On Scientific Approach for Senior High School Grade XI Students - Vayolin Eroika; Ramadhan Sumarmin; Helendra Helendra; Elsa Yuniarti (Universitas Negeri Padang, 2019)
On the curriculum of 2013, students are encouraged to perform the steps in the process of scientific or scholarly learning. The learning process in high school Pembangunan Laboratorium UNP had been scientific approach but the book used by the students have not based scientific approach, yet then the topics in the book used the students has not been in accordance with the core competence and basic competence in the curriculum of 2013. Thus, the descriptive researchers doing research to see the need for developing a module of biology for students of Class XI high school. Analytical techniques used in this research is descriptive statistical. This form of analysis on activities of observation, the definition of collection problems that occur in the learning process. Needs analysis to develop module are curriculum analysis, analysis of problems in learning, and analysis of learning materials. Research results are those of the third there is a lack of analysis, books used in schools has not been in accordance with the curriculum of 2013. There is a deficiency in basic competence 3.2 and 4.2 on Bioprocess cell topics, books used in schools have not provided scientific/scientific approach which scientific approach/scientific can enhance the learning interest of students so that learning process went smoothly, and the analysis of the three. then the lack of one of the solutions is to develop of biology module based on scientific approach on Bioprocess cell topics.